2016
DOI: 10.1038/ijos.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Second premolar agenesis is associated with mandibular form: a geometric morphometric analysis of mandibular cross-sections

Abstract: The aim of this study was to compare mandibular form (i.e., size and shape) between patients with agenesis of the lower second premolar (P2) and a control group with no agenesis. Three hypotheses were tested: (H1) agenesis causes a change in mandibular morphology because of inadequate alveolar ridge development in the area of the missing tooth (mandibular plasticity); (H2) agenesis is caused by spatial limitations within the mandible (dental plasticity); and (H3) common genetic/epigenetic factors cause agenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…Similar observations with those in the present study have been previously made in regard with patients with congenitally missing lower second premolars, where the bucco‐lingual alveolar ridge width and mandibular cross‐sectional area at the adjacent teeth were also significantly reduced compared to patients with fully erupted second premolars (Bertl et al. ). In this context, reduced development of regions adjacent to agenesis sites may also in some cases be due to a common genetic background of tooth agenesis (Graber ; Brook ; Al‐Nimri & Gharaibeh ; Alves‐Ferreira et al.…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations with those in the present study have been previously made in regard with patients with congenitally missing lower second premolars, where the bucco‐lingual alveolar ridge width and mandibular cross‐sectional area at the adjacent teeth were also significantly reduced compared to patients with fully erupted second premolars (Bertl et al. ). In this context, reduced development of regions adjacent to agenesis sites may also in some cases be due to a common genetic background of tooth agenesis (Graber ; Brook ; Al‐Nimri & Gharaibeh ; Alves‐Ferreira et al.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, no evaluation of the possible impact of the mesio‐distal gap on the bucco‐oral dimension was performed. On the other hand, a geometric morphometric evaluation of the whole mandibular cross‐section in the current group of patients (Bertl, Bertl et al., ) revealed that cross‐sectional mandibular size and shape differed significantly between patients with and without P2 agenesis, and that the differences extended beyond a localized morphological change at the agenesis sites, and involved the neighboring teeth and body of the mandible. Nevertheless, the average mesio‐distal crown dimension of the primary second molar is about 10 mm (Harris & Lease, ); the fact that in the present material in the AWO group straightforward placement of an implant, which was about 1 mm larger in Ø comparing to what was simulated in the above‐mentioned study (Bertl, Grotthoff et al., ), was possible in 50% of the cases and may indicate that the dimensions of the alveolar bone in the posterior aspects of the jaws are relatively less influenced by agenesis comparing to the anterior aspects.…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, it would be not surprising to diagnose aplasia of wisdom teeth in patients showing this distinct osseous dysplasia [ 66 ]. Indeed, the mandibular form is associated with the agenesis of premolars [ 67 ]. However, complete development of all three molars in deformed jaws is well-known for NF1 [ 6 , 12 , 13 ], although a reduced number of molars in the affected facial region is well-documented [ 11 ].…”
Section: Discussionmentioning
confidence: 99%